Comparison of static and dynamic balance between netball and volleyball in female athletes of UniKL RCMP - Mazelan, Fakhrul Haqimie; Eswaramoorthi, Vijayamurugan (Faculty of Sports Science and Recreation, 2025)
Balance is crucial for how a person moves, involving the interaction of the body systems to keep us stable. It is not just the ability to stand upright then extends to holding stationary positions as well as dynamic activities like walking, running, and other forms of locomotion, balance is about capably controlling the body's center of mass about its base of support. The body continually alters muscles and joints in an upright position to maintain its balance and avoid falling due to gravity. To maintain our upright posture and prevent accidents the nervous system controls small changes in our muscles and joints. Balance becomes essential when moving around a lot, such as when playing sports or on uneven surfaces to keep the body stable and prevent any injuries. This study aims to compare the balance abilities of female athletes in two sports, netball and volleyball, at UniKL RCMP.